Adição aos jogos digitais: uma investigação psicanalítica - Nogara, Michel Andrew (2020)
This thesis is the result of the research work involving players addictedto digital games. For this, we undertook a psychoanalytic investigation using the netnographic method. We designated the importance of the game for the constitution of the subject and its role in repetition through signifier opposition, therefore, in the formation of the addict's symptoms. The addition to digital games is part of a specific niche of psychopathologies, notably an addiction without substance, becoming a part of the new symptoms that are characteristic of the transformations that have occurred since the middle of the 20th century. We emphasize the role of fantasy in these players and in their addition, where there is a possibility of fixing the subject by the object, in this case, an object petit a. The two dimensions of the signifier and fantasy are fundamental for understanding this addition in the game, but insufficient. Therefore, we were concerned with the jouissance involved in the game - a solitary jouissance, as well as with the creative and non-sense universe involved in these games. Finally, we analyzed group aspects of the players, where circulation of unusual aggression is a symptom that we pointed to as prevalent, as well as we noted their ideas about violence and the relation with digital games